Pengaruh Kesadaran Wajib Pajak dan Pengetahuan Perpajakan Terhadap Kepatuhan Membayar Pajak Bumi dan Bangunan di Kecamatan Rawalumbu Kota Bekasi - Nurazizah; Irawati (Jurnal Ilmu Administrasi Publik, 2025)
The phenomenon found in Bekasi, precisely in Rawalumbu District, is that the realization of land and building tax revenue has not reached the target. The purpose of this study was to determine how much influence taxpayer awareness and tax knowledge have on compliance with paying land and building tax in Rawalumbu District, Bekasi simultaneously. The population in this study were land and building taxpayers in Rawalumbu District, Bekasi. The sample uses was 400 respondents using the slovin formula. The data collection method used the distribution of questionnaires. This study used multiple linear regression analysis, validity test, reliability test and hypothesis testing. The results of this study indicated that taxpayer awareness has a positive effect on taxpayer compliance by 12.6% and tax knowledge has a positive effect on taxpayer compliance by 24.1% and taxpayer awareness and tax knowledge simultaneously affect compliance in paying land and building tax in Rawalumbu District, Bekasi City by 30%. Taxpayer compliance can be achieved with two variables: Taxpayer Awareness and Taxation Knowledge. Keywords Taxpayer Awareness, Taxation Knowledge, Taxpayer Compliance